Difficulties in using the MOODLE platform from the point of view of members of the teaching staff at Tishreen University (a field study in the College of Education) (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The study aimed to identify the difficulties of using the Moodle platform from the point of view of members of the teaching staff at the Faculty of Education at Tishreen University, where the study sample consisted of (50) members of the teaching staff at the Faculty of Education at Tishreen University. A questionnaire consisting of three axes (difficulties related to members of the educational staff, difficulties related to students, difficulties related to infrastructure), each axis includes a number of items, the study used the descriptive approach, and the results showed that the most difficult difficulties experienced by members of the educational staff from their point of view The lack of conviction in the effectiveness of the Moodle platform for the member of the educational staff, and the difficulty of the student's inability to understand the study material through the platform, which came with a high degree. (Academic degree, number of years of experience, gender ) .